Pengaruh Komtmen Guru dan Motivasi Kerja terhadap Profesionalisme Guru Sekolah Dasar Katolik di Kota Ende - Maria Finsensia Ansel; Yohana Nono BS (Departement of Mathematics Education, 2023)
The teacher is the spearhead of the process of implementing education in schools. Teachers are required to be professional in carrying out their duties and responsibilities in the learning process. This study aims to determine the effect of teacher commitment and work motivation on the professionalism of Catholic elementary school teachers in the city of Ende. This research method is quantitative research with data collection techniques using questionnaires or questionnaires in the form of questionnaires about teacher commitment, work motivation, and teacher professionalism. Respondents in this study were teachers at a Catholic elementary school in the city of Ende. The number of samples in this study were 52 people. The results showed that teacher commitment and work motivation had a significant effect on teacher professionalism where a significance value of 0.000 <0.05 and an R square value of 0.405 means that the influence of teacher commitment and work motivation on teacher professionalism is 40.5%. In conclusion, the higher the teacher's commitment and work motivation, the higher the teacher's professionalism and conversely the lower the teacher's commitment and work motivation, the lower the teacher's professionalism.